Efektivitas Teknik Role Playing Untuk Mereduksi Perilaku Taunting (Ejekan) Siswa Kelas VIII B SMPN 1 Sukorambi Jember - Halimatus Sa’diyah; Weni Kurnia Rahmawati; Imaratul Ulwiyah (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2024)
The research examines the effectiveness of the role playing method to reduce taunting or teasing of students in class VIII B SMPN 1 Sukorambi Jember. This type of research is quantitative research. The population was all students of class VIII B at SMPN 1 Sukorambi Jember with a sample of 6 students. Data collection methods using observation, interviews and questionnaires. Taunting is a form of verbal intimidation that aims to undermine a person's self-esteem, this behaviour often occurs in early adolescence. The data analysis method used is the Wilcoxon test and is measured using SPSS version 25.0 for windows. The type of research used is Quasi experiment with Equivalent Time Series one group pre-test post-test method. Based on the results of the wilcoxon test calculation, the Asymp. Sig 0.027 <0.05, the conclusion is that the hypothesis is accepted because there is a decrease in the level of taunting behaviour at SMPN 1 Sukorambi Jember after treatment.